2020
DOI: 10.3892/ijmm.2020.4553
|View full text |Cite
|
Sign up to set email alerts
|

CDK5 inhibition in�vitro and in vivo induces cell death in�myeloma and overcomes the obstacle of bortezomib resistance

Abstract: The emergence of new drugs is a major feature of the treatment history of multiple myeloma (MM), which also reflects the current incurability of MM. As a unique member of cyclin dependent kinase (cdK) family, cdK5 participates in numerous tumorigenic or non-tumorigenic processes. The aim of this study is to investigate the effects of cdK5 on the viability of MM cells and bortezomib resistance using western blotting, immunohistochemistry, transient transfection, MTT assays, cell cycle analysis, apoptosis assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Hence, the combination of both drugs changes the intracellular balance to favor apoptosis. P276-00 was tested together with Bortezomib in myeloma cells and showed marked synergism [ 34 ], which coincides with the results of SLM-6 [ 86 ] and Dinaciclib [ 87 ]. The combination of Doxorubicin, Bortezomib and either P276-00 [ 34 ] or Seliciclib [ 59 ] were also deemed effective.…”
Section: Potential Synergistic Combinations With Cdk9 Inhibitors In Multiple Myelomasupporting
confidence: 58%
See 1 more Smart Citation
“…Hence, the combination of both drugs changes the intracellular balance to favor apoptosis. P276-00 was tested together with Bortezomib in myeloma cells and showed marked synergism [ 34 ], which coincides with the results of SLM-6 [ 86 ] and Dinaciclib [ 87 ]. The combination of Doxorubicin, Bortezomib and either P276-00 [ 34 ] or Seliciclib [ 59 ] were also deemed effective.…”
Section: Potential Synergistic Combinations With Cdk9 Inhibitors In Multiple Myelomasupporting
confidence: 58%
“…A synergy between CPI-203, a novel bromodomain inhibitor, and either Bortezomib or Lenalidomide was also observed [ 86 , 87 ]. Lenalidomide contributes to overcoming resistance to Bortezomib via inhibition of IRF4, which leads to MYC downregulation [ 93 ].…”
Section: Potential Synergistic Combinations With Cdk9 Inhibitors In Multiple Myelomamentioning
confidence: 99%
“…Single-point mutations and modification of gene expression in neoplastic cells refractory to PI have been reported in previous studies [11,[13][14][15][16][17]. Several genes associated with bortezomib resistance have been identified in MM cells, including POMP, XBP1, PSMB5, MARCKS, ABCB1, CXCR4, MAF, TXN, TJP1, RPL5, CDK5 and CYP1A1 [18][19][20][21][22][23][24][25]; however, these genes have been examined individually, and usually only using commercially-available MM cell lines. The present study comprehensively examines the mRNA expression of nine previously-described genes that may affect resistance in patients with a clinicallydetected loss of response to PI treatment: ABCB1, CXCR4, MAF, MARCKS, POMP, PSMB5, RPL5, TXN and XBP1.…”
Section: Introductionmentioning
confidence: 91%
“…Our findings demonstrated that serum expression of several miRNAs differs between patients who are refractory to bortezomib and those who are sensitive. However, it is important to examine the roles of these miRNAs in the regulation of recently-identified genes associated with bortezomib resistance, such as PSMB5 , CDK5 and CYP1A1 , in MM cells [ 81 , 82 , 83 ]. It has been reported previously that miRNAs can modulate the expression of genes responsible for bortezomib refractoriness in MM cells; for example, CDK5 expression may be related to miR-27a-5p activity [ 84 ].…”
Section: Discussionmentioning
confidence: 99%